Appearance of Florid Cemento-Osseous Dysplasia on SPECT/CT. (May 2019) - Yang, Dorothy Daiyi; Ghuman, Abeer; Stratton, Richard; Hall, Margaret; Parthipun, Arum
Abstract : Abstract: Florid cemento-osseous dysplasia, a benign fibro-osseous condition, is diagnosed based on characteristic radiographic appearances of multifocal round or lobulated sclerotic lesions associated with the teeth in multiple quadrants of the jaws. We report a case of a 73-year-old woman who presented with a painless sharp bony area on the right side of her maxilla. SPECT/CT of facial bones demonstrated multifocal intense increased uptake in both the maxilla and mandible, corresponding to ill-defined florid sclerotic periapical lesions seen on CT, in keeping with a classical appearance of florid cemento-osseous dysplasia.